Digitisation for access to preserved documents - Bremer-Laamanen, Majlis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Today the digitisation of our collections is a goal for libraries all over Europe. The choices we make in digitisation and preservation now will have a significant impact on the future. Do we only emphasise access? How do we enable access and preserve our originals in a qualitative and productive way? What will actually be left of our cultural heritage in the next millennium? In this paper I am going to look at promoting access to preserved originals mirrored by the experience at the Helsinki University Library, the National Library of Finland: · Preservation activities as platform for digitisation and OCR · Processing access to collections · The future - looking ahead